SOLUTION
Given the question in the image, the following are the solution steps to answer the question.
STEP 1: Write the given question.
![0.06*10^(-1)O\text{ }0.6*10^(-2)](https://img.qammunity.org/2023/formulas/mathematics/college/xhmzicmovj49yyyaq8ejle3s7trvz5dzxf.png)
STEP 2: Divide the expression into two parts and solve each parts to get their results
![\begin{gathered} 0.06*10^(-1)\Rightarrow\text{?} \\ 0.6*10^(-2)\Rightarrow\text{?} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/rujt3x7pha1rqy0ce1yr4klu8jpkdk2aby.png)
STEP 3: Solve the first expression
![\begin{gathered} 0.06*10^(-1) \\ 0.06*10^(-1) \\ =0.06*(1)/(10) \\ \mathrm{Multiply\: fractions}\colon\quad \: a*(b)/(c)=(a\:*\:b)/(c) \\ =(1*\:0.06)/(10) \\ \mathrm{Multiply\: the\: numbers\colon}\: 1*\: 0.06=0.06 \\ =(0.06)/(10) \\ \mathrm{Divide\: the\: numbers\colon}\: (0.06)/(10)=0.006 \\ =0.006 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/gyg5i7bvxe11w64c66csaautkyy8ip1fjg.png)
STEP 4: Solve the second expression
![\begin{gathered} 0.6*10^(-2) \\ \mathrm{Apply\: exponent\: rule}\colon\quad \: a^(-b)=(1)/(a^b) \\ \mathrm{Multiply\: fractions}\colon\quad \: a*(b)/(c)=(a\:*\:b)/(c) \\ =(1*\:0.6)/(10^2) \\ \mathrm{Multiply\: the\: numbers\colon}\: 1*\: 0.6=0.6 \\ =(0.6)/(10^2) \\ 10^2=100 \\ =(0.6)/(100) \\ \mathrm{Divide\: the\: numbers\colon}\: (0.6)/(100)=0.006 \\ =0.006 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/5j1zox4z9x44a41xm3cpnv0usjeb9snw1o.png)
STEP 5: Compare the two results from the simplified expressions
![\begin{gathered} \text{0}.006\Rightarrow0.006 \\ It\text{ can be se}en\text{ that the expression on the right hand side is equal to the expression on the left hand side} \end{gathered}]()
Hence,
![0.06*10^(-1)=\text{ }0.6*10^(-2)](https://img.qammunity.org/2023/formulas/mathematics/college/f2tbxcwj3vqt1nc7l2xemmwuqa6gqjqn2y.png)
Equal sign(=)